The Impact of Technological System Usability on Customer Relationship Management Practices in Telecommunication Companies in Benadir Region, Mogadishu, Somalia - Aweis Ahmed Hussein Jarras; Abdimalik Aden Ibrahim (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2026)
This study explored how the usability of technological systems affects Customer Relationship Management (CRM) practices in the telecommunications industry in the Benadir Region, Mogadishu, Somalia. A descriptive research design with quantitative methods was employed. Data were collected from 100 employees in the telecommunications sector. The study employed questionnaires distributed through Google Forms to assess the impact of user-friendly CRM interfaces on adoption and usage, evaluate the training duration required for proficiency, and examine how system speed and functionality influence productivity. The results showed that 80% of users found the CRM interface intuitive and easy to learn, 28% were neutral, and 9% were dissatisfied with the clarity of error messages. Furthermore, 55% of users had less than a year of CRM experience, emphasizing the necessity of role-specific training. Although 71% of participants praised real-time analytics and 80% found automation beneficial, only 57% believed that CRM improved overall productivity, suggesting contextual challenges in achieving efficiency improvements. The predominantly young (65% aged 26-45), male (67%), and inexperienced user group highlights the need for inclusive design and phased onboarding. The recommendations include redesigning error messages, implementing tiered training, and enhancing mobile functionality for low-bandwidth settings. This study adds to CRM usability research by combining human-centered design principles with technology acceptance frameworks and identifying a "usability-proficiency gap" in fragile economies. The practical implications for telecom managers involve actionable strategies to boost CRM adoption and effectiveness within Somalia's unique infrastructure and workforce context.